Pentingnya Perusahaan Mengelola Hubungan Baik dan Fungsional dengan Pemangku Kepentingan - Arie I. Chandra (Jurnal Administrasi Bisnis, 2009)
The face of business in today’s society is ever changing, highly dynamic and extraor-dinarily diverse. Some events are exciting, others depressing.But many reflect thebasic trends and underlying forces that shaping business and its stake holders.Thereare a complex relationship between competitor, government and mass media.Everybusiness has complex involvements with other people, groups and organizations inthe external environment. This article describes the connection between broad, ab-stract ways of thinking about business and the rest of the world relationship andspecific- practical ways of doing so.Keywords: Pemangku Kepentingan (Stake holder), Pesaing dan Aliansi, KebijakanPublik dan Manajemen Pemangku Kepentingan